Chapter 1
Solving Equations and Inequalities
1.1 – Expressions and Formulas
Order of Operations
1.1 – Expressions and Formulas Order of Operations Parentheses
1.1 – Expressions and Formulas Order of Operations Parentheses Exponents
1.1 – Expressions and Formulas Order of Operations Parentheses Exponents Multiplication
1.1 – Expressions and Formulas Order of Operations Parentheses Exponents Multiplication Division
1.1 – Expressions and Formulas Order of Operations Parentheses Exponents Multiplication Division Addition
1.1 – Expressions and Formulas Order of Operations Parentheses Exponents Multiplication Division Addition Subtraction
1.1 – Expressions and Formulas Order of Operations ParenthesesPlease Exponents Multiplication Division Addition Subtraction
1.1 – Expressions and Formulas Order of Operations ParenthesesPlease ExponentsExcuse Multiplication Division Addition Subtraction
1.1 – Expressions and Formulas Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy Division Addition Subtraction
1.1 – Expressions and Formulas Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy DivisionDear Addition Subtraction
1.1 – Expressions and Formulas Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy DivisionDear AdditionAunt Subtraction
1.1 – Expressions and Formulas Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy DivisionDear AdditionAunt SubtractionSally
Example 1
Find the value of [2(10 - 4) 2 + 3] ÷ 5.
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 =
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5 [72 + 3] ÷ 5
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5 [72 + 3] ÷ 5 75 ÷ 5
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5 [72 + 3] ÷ 5 75 ÷ 5 15
Example 2
Evaluate x 2 – y(x + y) if x = 8 and y = 1.5.
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) =
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( )
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( )
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5)
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5) 64 – 1.5(9.5)
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5) 64 – 1.5(9.5) 64 – 14.25
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5) 64 – 1.5(9.5) 64 –
Example 3
Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = c 2 – 5
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3)
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5 = – 5
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5 = – 5 = 32 4
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5 = – 5 = 32 = 8 4
Example 4
Find the area of the following trapezoid. 16 in. 10 in. 52 in.
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in.
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 )
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. = h 52 in. A = ½h(b 1 + b 2 )
Example 4 Find the area of the following trapezoid. 16 in. = b 1 A = ½h(b 1 + b 2 ) 10 in. = h 52 in. A = ½h(b 1 + b 2 )
Example 4 Find the area of the following trapezoid. 16 in. = b 1 A = ½h(b 1 + b 2 ) 10 in. = h 52 in. = b 2 A = ½h(b 1 + b 2 )
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( )
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( ) = ½10(68)
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( ) = ½10(68) = 5(68)
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b2) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( ) = ½10(68) = 5(68) = 340
1.2 – Properties of Real Numbers
Real Numbers
1.2 – Properties of Real Numbers Real Numbers (R)
1.2 – Properties of Real Numbers Real Numbers (R)
1.2 – Properties of Real Numbers Real Numbers (R) Rational
1.2 – Properties of Real Numbers Real Numbers (R) Rational (⅓)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) Integers
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) Integers (-6)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) Whole #’s
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) Whole #’s (0)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) (W) Whole #’s (0)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) (W) Whole #’s (0)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) (W) Whole #’s (0) Natural #’s
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) (W) Whole #’s (0) Natural #’s (7)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) (W) Whole #’s (0) (N) Natural #’s (7)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (Z) Integers (-6) (W) Whole #’s (0) (N) Natural #’s (1)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) Irrational (Z) Integers (-6) (W) Whole #’s (0) (N) Natural #’s (1)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) Irrational √ 5 (Z) Integers (-6) (W) Whole #’s (0) (N) Natural #’s (1)
1.2 – Properties of Real Numbers Real Numbers (R) (Q) Rational (⅓) (I) Irrational √ 5 (Z) Integers (-6) (W) Whole #’s (0) (N) Natural #’s (1)
Real Rational Irrational Integers Whole Natural
Example 1
Name the sets of numbers to which each apply.
Example 1 Name the sets of numbers to which each apply.
Example 1 Name the sets of numbers to which each apply.
Example 1 Name the sets of numbers to which each apply. (a) √ 16
Example 1 Name the sets of numbers to which each apply. (a) √ 16 = 4
Example 1 Name the sets of numbers to which each apply. (a) √ 16 = 4 - N
Example 1 Name the sets of numbers to which each apply. (a) √ 16 = 4 - N, W
Example 1 Name the sets of numbers to which each apply. (a) √ 16 = 4 - N, W, Z
Example 1 Name the sets of numbers to which each apply. (a) √ 16 = 4 - N, W, Z, Q
Example 1 Name the sets of numbers to which each apply. (a) √ 16 = 4 - N, W, Z, Q, R
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b)-185
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R (d) -⅞
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R (d) -⅞ - Q
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R (d) -⅞ - Q, R
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R (d) -⅞ - Q, R __ (e) 0.45
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R (d) -⅞ - Q, R __ (e) Q
Example 1 Name the sets of numbers to which each apply. (a)√ 16 = 4 - N, W, Z, Q, R (b) Z, Q, R (c)√ 20 - I, R (d) -⅞ - Q, R __ (e) Q, R
Properties of Real Numbers PropertyAdditionMultiplication Commutativea + b = b + aa·b = b·a Associative (a+b)+c = a+(b+c) (a · b) · c = a · (b · c) Identitya+0 = a = 0+aa·1 = a = 1·a Inversea+(-a) =0= -a+aa·1 =1= 1·a a a Distributivea(b+c)=ab+ac and (b+c)a=ba+ca
Example 2
Name the property used in each equation.
Example 2 Name the property used in each equation. (a) (5 + 7) + 8 = 8 + (5 + 7)
Example 2 Name the property used in each equation. (a) (5 + 7) + 8 = 8 + (5 + 7) Commutative Addition
Example 2 Name the property used in each equation. (a) (5 + 7) + 8 = 8 + (5 + 7) Commutative Addition (b) 3(4x) = (3·4)x
Example 2 Name the property used in each equation. (a) (5 + 7) + 8 = 8 + (5 + 7) Commutative Addition (b) 3(4x) = (3·4)x Associative Multiplication
Example 3 What is the additive and multiplicative inverse for -1¾?
Example 3 What is the additive and multiplicative inverse for -1¾? Additive: -1¾
Example 3 What is the additive and multiplicative inverse for -1¾? Additive: -1¾ + = 0
Example 3 What is the additive and multiplicative inverse for -1¾? Additive: -1¾ + 1¾ = 0
Example 3 What is the additive and multiplicative inverse for -1¾? Additive: -1¾ + 1¾ = 0 Multiplicative: -1¾
Example 3 What is the additive and multiplicative inverse for -1¾? Additive: -1¾ + 1¾ = 0 Multiplicative: -1¾ · = 1
Example 3 What is the additive and multiplicative inverse for -1¾? Additive: -1¾ + 1¾ = 0 Multiplicative: (-1¾)(- 4 / 7 ) = 1
Example 4
Simplify 2(5m+n)+3(2m–4n).
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n)
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n)
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n)
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m +
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n +
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m –
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m – 12n
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m – 12n
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m – 12n
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m – 12n 10m + 6m + 2n – 12n
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m – 12n 10m + 6m + 2n – 12n 16m
Example 4 Simplify 2(5m+n)+3(2m–4n). 2 (5m+n) + 3 (2m–4n) 2(5m)+2(n)+3(2m)-3(4n) 10m + 2n + 6m – 12n 10m + 6m + 2n – 12n 16m – 10n